Mitigasi Risiko Operasional UMKM Pengelolaan Talas Desa Lenteng Timur Kabupaten Sumenep Pendekatan House of Risk - Maidatatia, Al; Destiarni, Resti Prastika; Widodo, Slamet; Sugiarti, Teti (Universitas Muhammadiyah Surakarta, 2024)
Production process of taro-chips is still unstable due to constraints in operational section, like raw taro materials that are not always available, causing the production process of taro-chips be carried out while waiting for raw taro materials to be available. Time gap between availability of taro-chips and consumer demand creates risks that affect business performance. This microbusiness must share results with BUMDes because it is a BUMDes-assisted business. The purpose of research is identifying risks and sources in taro-chips MSME operational process assisted by BUMDes Lenteng Timur, analyzing of operational risk level using HOR (House of Risk) method, and determining mitigation strategies in reducing of potential risk occurrence. The research was conducted in Lenteng Timur Village, with respondents are the owners and managers of taro-chips microbusinesses. The HOR phase 1 result obtained 12 risk events and 7 risk sources (risk agents), which are prioritized into 4 priority risk sources, which can be used to carry out risk mitigation actions. In HOR phase 2, 5 mitigation strategies can be done to overcome priority risks. These mitigation strategies can be conducted to overcome existing risks to reduce the potential for risk occurrence in operational activities that affect the production of taro-chips.